Efficacy of interactive instructional strategies on students’ academic achievement and attitude toward computer networking - Odekeye, Ola; Jita, Thuthukile (Journal of Interdisciplinary Studies in Education, 2026)
This study examined the efficacy of interactive instructional strategies in learning computer networking among secondary school students in Lagos State, Nigeria. A quasi-experimental design involving 161 computer students from three purposively selected schools. Two experimental and one control group. The Computer Network Achievement Test and Computer Network Student Attitude Questionnaire were used to collect quantitative data, with reliability indices of .88 and .84, respectively. In contrast, qualitative data were collected using a semi-structured interview guide from five participants in each experimental group. The findings show higher mean performance among students in the experimental group than in the control group. There was also a statistically significant difference in achievement (F(2, 156) = 378.85) and attitude (F(2, 156) = 9.99), both at p < .05, between the experimental and the control groups. This indicates the efficacy of the strategies, thus helping students become active participants in their learning.